POLYLACTIC/POLYGLYCOLIC ACID COPOLYMER IS A GOOD CARRIER FOR BMP-2 ON BONE REGENERATION? - Veloso dos Anjos, Alexandre Ladeira; Perez, Roble Casares; Braga, Barbara Maciel; Matsumoto, Mariza Akemi [UNESP]; Okamoto, Roberta [UNESP]; Saraiva, Patricia Pinto; Silva, Andreia Aparecida da; Pegoraro, Thiago Amadei (Univ Federal Uberlandia, 2017)
The aim of this work was to evaluate the role of polylactic /polyglycolic acid copolymer as carrier for BMP-2 on bone regeneration in rat calvarium. Forty five adult male rats underwent 5-mm critical defects in bone calvaria to be divided into three groups according to the filling materials: Control-blood clot; PLGA-polylactic acid Polyglycolic/copolymer; PLGA + BMP-2 -polylactic acid Polyglycolic/copolymer associated with BMP-2. Sacrifice of animals occurred at 5, 15 and 30 days after surgery The evaluation of new bone formation was obtained by histomorphometry, while OPG and RANKL proteins were observed by immunohistochemistry. Statistical analysis was performed by means of nonparametric tests based on quantitative variables of independent samples. Considering the amount of newly formed bone, significant difference was detected between PGLA (178,2 +/- 137,5 mu m) and the other groups, at day 30. In PLGA + BMP-2 and control groups, the expression of RANKL was prevalent on the OPG in the periods of 15 and 30 days, suggesting a favorable condition for bone reabsorption in these periods. Therefore, immunoexpression of RANKL and OPG and bone formation observed in different groups and periods of analysis showed that the polylactic/polyglycolic acid copolymer does not act as a good carrier for BMP-2.
Keywords: Bone tissue; Osteoprotegerin; RANKL; Immunohistochemistry